ABO blood groups as determinants to patient outcomes in SARS-CoV-2 - Robinson, Jared; Banerjee, Indrajit; Sathian, Brijesh; Leclézio, Alexandra; Roy, Bedanta (Journal of Biomedical Sciences, 2020)
Background: Blood group antigens are present on the red blood cell surface. O, A, and B are the major blood groups. A, B, AB, and A1 are the antigens. An ample amount of research supports the close association of blood groups with diseases. A new school of thought and finding seems to be indicating that certain blood groups are more susceptible to the COVID-19 infection in comparison to others. Current evidence suggests that SARS-CoV-2 positive cases are more prevalent in individuals with blood group A as compared to those with blood group O. This finding, however, was only relevant for the Rh (+ve) positive blood types. Genetic association reveals that the ABO blood group locus and a chromosome 3 gene cluster are associated with severe acute respiratory syndrome in coronavirus (SARS-CoV-2) respiratory failure patents. This was found in an Italian- Spanish genome-wide association analysis. Various associations between the patients' blood groups when comparing the data with that of physiologically healthy individuals from the same geographical region helped to get a clear comparative picture. Associations that were cross-replicating in nature were determined at chromosome 3p21.31 and chromosome 9q34. The association at chromosome 9q34 was identified at the ABO blood group locus. The difference in the susceptibility could be correlated to the circulating anti‐A antibodies, which inhibit or interfere with the virus-cell adhesion process. Conclusion: It is evident that the research conducted to date is supportive and does suggest that humans of the Blood group O are less likely to be infected in the COVID-19 pandemic as when compared to other blood groups. The SARS-CoV-2 situation is evolving rapidly, discoveries and anomalies are being reported daily. Therefore, it is advised that more definitive and consolidatory research is to be conducted to further elucidate the underlying mechanism of action for the protection in blood group O.